Banks' equity stakes and lending: Evidence from a tax reform - Bastian von Beschwitz; Daniel Foos (Deutsche Bundesbank, 2018)
Several papers find a positive association between a bank's equity stake in a borrowing firm and lending to that firm. While such a positive cross-sectional correlation may be due to equity stakes benefiting lending, it may also be driven by endogeneity. To distinguish the two, we study a German tax reform that permitted banks to sell their equity stakes tax-free. After the reform, many banks sold their equity stakes, but did not reduce lending to the firms. Thus, our findings question whether prior evidence can be interpreted causally and suggest that banks' equity stakes may be less important for lending than previously thought.
Keywords: G21; G32; 330; Relationship banking; Ownership; Monitoring